2012
DOI: 10.1021/pr201036j
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Diversity of Progressive Kidney Disease in 325 Patients with Type 1 Diabetes (the FinnDiane Study)

Abstract: Type 1 diabetic patients with varying severity of kidney disease were investigated to create multimetabolite models of the disease process. Urinary albumin excretion rate was measured for 3358 patients with type 1 diabetes. Prospective records were available for 1051 patients, of whom 163 showed progression of albuminuria (8.3-year follow-up), and 162 were selected as stable controls. At baseline, serum lipids, lipoprotein subclasses, and low-molecular weight metabolites were quantified by NMR spectroscopy (32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 50 publications
(60 reference statements)
2
58
0
1
Order By: Relevance
“…The n-3 PUFAs docosahexaenoic acid and eicosapentaenoic acid were detected on our platform, yet we did not find significant differences in these PUFAs between the DR group and control subjects with diabetes in the discovery set (Supplementary Table 8). Similarly, Mäkinen et al (41) found that the baseline serum docosahexaenoic levels did not predict progressive kidney disease among patients with type 1 diabetes. Although n-3 PUFAs have been shown to protect against DR in rodent models (42,43), their efficacy in preventing vascular complications of diabetes can only be proven through randomized controlled trials.…”
Section: Nonreplicable Metabolite Markers Of Drmentioning
confidence: 96%
“…The n-3 PUFAs docosahexaenoic acid and eicosapentaenoic acid were detected on our platform, yet we did not find significant differences in these PUFAs between the DR group and control subjects with diabetes in the discovery set (Supplementary Table 8). Similarly, Mäkinen et al (41) found that the baseline serum docosahexaenoic levels did not predict progressive kidney disease among patients with type 1 diabetes. Although n-3 PUFAs have been shown to protect against DR in rodent models (42,43), their efficacy in preventing vascular complications of diabetes can only be proven through randomized controlled trials.…”
Section: Nonreplicable Metabolite Markers Of Drmentioning
confidence: 96%
“…All standard statistical approaches can be applied in a straightforward manner, including adjustments for potential confounding factors 6 , 22 , 24 , 25 , 28 . Of course, as with any quantitative molecular data, the analyses are by no means limited to standard approaches but, for example, multivariate non-linear approaches, 76 , 77 network analyses, 77 , 78 pathway approaches 79 , 80 and integration of multi-omic data 26 , 47 , 75 , 81–86 are all feasible. In fact, this is in contrast to spectral-based approaches in which these types of analyses, aiming for detailed biological understanding, would mostly be impossible to perform and interpret at the molecular level.…”
Section: Quantitative Molecular Data–the Base For a Multitude Of Statmentioning
confidence: 99%
“…In addition to predicting risk of developing diabetes, the degree of lipid saturation has been linked to diabetes complications. NMR metabonomics with baseline serum from subjects in the Finnish Diabetic Nephropathy (FinnDiane) Study linked high levels of saturated fatty acids in serum to accelerated progression of kidney disease in patients with type 1 diabetes (79). …”
Section: Metabolomics and Diabetes Researchmentioning
confidence: 99%